2021
DOI: 10.14202/vetworld.2021.1241-1246
|View full text |Cite
|
Sign up to set email alerts
|

Seroprevalence and risk factors of West Nile virus infection in veterinarians and horses in Northern Palestine

Abstract: Background and Aim: West Nile fever (WNF) is a neurotropic, mosquito-borne disease affecting humans and domesticated animals, caused by a member of the genus Flavivirus. Over the last decades, this virus has been responsible for several cases of illness in humans and animals. The current epidemiological status of WNF in horses is insufficient, and in veterinarians, as an occupational hazard is unknown. This study aimed to investigate and determine the seroprevalence and risk factors for WNF in veterinarians an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 26 publications
0
7
0
Order By: Relevance
“…Farmers, agricultural workers, veterinarians and in general jobs in contact with birds and farm animals have also been identified as occupational groups at higher risk for WNV infection. Alzuheir et al [ 23 ] detected a 23.0% WNV seroprevalence among veterinarians in Palestine, which was much higher than that observed in other non-occupational groups from other studies where seropositivity was not associated with either sector of work. Although horses are ‘dead-end’ hosts which do not sustain the circulation of the WNV in nature, veterinarians in the equine specialty have been suggested as the first sentinel of human cases in WNV-infected horses’ areas.…”
Section: Discussionmentioning
confidence: 86%
See 2 more Smart Citations
“…Farmers, agricultural workers, veterinarians and in general jobs in contact with birds and farm animals have also been identified as occupational groups at higher risk for WNV infection. Alzuheir et al [ 23 ] detected a 23.0% WNV seroprevalence among veterinarians in Palestine, which was much higher than that observed in other non-occupational groups from other studies where seropositivity was not associated with either sector of work. Although horses are ‘dead-end’ hosts which do not sustain the circulation of the WNV in nature, veterinarians in the equine specialty have been suggested as the first sentinel of human cases in WNV-infected horses’ areas.…”
Section: Discussionmentioning
confidence: 86%
“…( Table 3 ). Moreover, the study by Dorko et al [ 25 ] and Alzuheir et al [ 23 ] showed a probably high risk of bias in more than two of the domains. Overall, however, the studies make it possible to adequately assess the results obtained from the literature review.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…More than 53 mosquito species have been identified as possible vectors for RVFV [26], including Phlebotomus papatasi and Aedes albopictus in Palestine [27,28]. These vectors are related to the endemic circulation of other arboviral diseases in Palestine, like West Nile fever in humans and animals, and bluetongue in ruminants [29,30]. Controlling such a disease requires a strategy like the One Health approach, which involves understanding and managing the animal, human, and environmental determinants of the disease [10].…”
Section: Sample Variables Are Shown In Table-1mentioning
confidence: 99%
“…Understanding the factors responsible for the absence of RVFV could provide valuable information to prevent and control the disease in a region infested by the vector but lacking the virus [25]. Our findings provide a baseline for future prediction and early warning systems for RVFV emergence.< Spatial and temporal surveillance of the vectors and susceptible animals will facilitate early warning [25][26][27][28][29][30][31][32].…”
Section: Sample Variables Are Shown In Table-1mentioning
confidence: 99%